2022
DOI: 10.1002/hsr2.582
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital administration of broad‐spectrum antibiotics for sepsis patients: A systematic review and meta‐analysis

Abstract: Background and Aims Some studies have suggested that earlier initiation of antibiotics has shown positive outcomes in sepsis patients. We aimed to do a systematic review and meta‐analysis to evaluate the effect of prehospital administration of antibiotics on 28 days mortality and length of stay in hospital and intensive care unit for sepsis patients. Methods We formulated a search strategy and used it on search databases PubMed, Scopus, Web of Science, and Embase. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…For the secondary outcomes of length of stay for hospital generally and ICU, there was no evidence of good quality at low risk of bias to indicate reductions favouring prehospital administration of antibiotics. The conclusions drawn here differ from those drawn by Varney et al 18 in a 2022 systematic review and meta-analysis, who concluded that receiving prehospital antibiotics can significantly lower mortality in sepsis patients compared to patients who do not receive prehospital antibiotics. The authors meta-analysed four studies reporting comparisons between prehospital antibiotics and usual care (two RCTs and two observational), reporting a risk ratio (RR) favouring prehospital antibiotics (RR 0.81; 95% CI 0.68-0.97; p = 0.02).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…For the secondary outcomes of length of stay for hospital generally and ICU, there was no evidence of good quality at low risk of bias to indicate reductions favouring prehospital administration of antibiotics. The conclusions drawn here differ from those drawn by Varney et al 18 in a 2022 systematic review and meta-analysis, who concluded that receiving prehospital antibiotics can significantly lower mortality in sepsis patients compared to patients who do not receive prehospital antibiotics. The authors meta-analysed four studies reporting comparisons between prehospital antibiotics and usual care (two RCTs and two observational), reporting a risk ratio (RR) favouring prehospital antibiotics (RR 0.81; 95% CI 0.68-0.97; p = 0.02).…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, the methodological and clinical heterogeneity present amongst the studies included by Varney et al suggest that a combined meta-analysis was inappropriate. Combining observational and clinical trials in a single meta-analysis requires complex analytic modelling using meta-regression or quality effects modelling 36 ; this appears not to have been addressed in Varney et al, 18 hence the overall meta-analysis result favouring prehospital antibiotics should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antibiotics could more routinely be administered in the prehospital setting. A recent metaanalysis found a significant reduction in the 28-day mortality rate when patients received a first dose of a broad-spectrum antibiotic in the prehospital field compared to standard care [17]. An acceleration of the management of patients where the diagnosis has already been made is probably the easiest way to further improve outcomes.…”
mentioning
confidence: 99%